Methods of testing plastics. Thermal properties. Determination of temperature of deflection under a bending stress of 1.8 MPa, of plastics and ebonite. Determination of temperature of deflection under a bending stress of 0.45 MPa, of plastics and ebonite. Determination of temperature of deflection under a bending stress, of rigid thermosetting resin bonded laminated sheet Part 1 Methods 121A to 121C, (29th October 1976) - British Standards Institution,
No abstract available